2016
DOI: 10.3389/fmicb.2016.02020
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Conservation and Diversification of Metarhizium Species Correlate with Fungal Host-Specificity

Abstract: The ascomycete genus Metarhizium contains several species of insect pathogenic fungi ranging from specialists with narrow host ranges to generalists that can infect diverse invertebrates. Genetic and metabolic conservations and diversifications of Metarhizium species are not well understood. In this study, using the genome information of seven Metarhizium species, we performed a comparative analysis of gene clusters involved in secondary metabolisms (SMs) in these species. The results revealed that the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 50 publications
5
29
0
1
Order By: Relevance
“…The smaller number suggests that MAC may rely on simple metabolites to improve its virulence against insects owing to the biosynthesis cost. MAC can produce other cytotoxic antibiotic metabolites [11], however the pathogenesis of such metabolites in contributing to the virulence of MAC still needs to be investigated.…”
Section: Plos Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller number suggests that MAC may rely on simple metabolites to improve its virulence against insects owing to the biosynthesis cost. MAC can produce other cytotoxic antibiotic metabolites [11], however the pathogenesis of such metabolites in contributing to the virulence of MAC still needs to be investigated.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Further comparative genomic analysis showed that MAC presents less virulence genes, including chitinase, protease, and secondary metabolic gene clusters [7]. Interestingly, MAC lacks the genes for the biosynthesis of the virulence factor destruxin compared with MAA [7,11]. In fact, destruxin allows MAA to inhibit the system activity of prophenoloxidase and the production of bactericidal peptides of hosts, suppressing the hosts' immune defense and increasing the opportunistic infection of microbes in host insects [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been demonstrated that DTX are dispensable for pathogenicity against some hosts (Donzelli et al ., ), while other Metarhizium spp. lack the DTX cluster entirely (Xu et al ., ). This suggests that other as‐yet unidentified insecticidal SMs may play analogous roles in these species.…”
Section: Introductionmentioning
confidence: 97%
“…. Furthermore, Xu et al (2016) recently demonstrated an association between evolution of modern generalist Metarhizium spp. and acquisition of this DTX cluster, suggesting a role for DTX in adaptation to a wider host-range.…”
Section: Introductionmentioning
confidence: 99%